Alternative splicing event associated with immunological features in bladder cancer - Yu, Xinbo; Luo, Bixian; Lin, Jianwei; Zhu, Yu (Frontiers in Oncology, 2023)
Objective: Bladder cancer (BLCA), the most prevalent urinary tumor, has few treatments. Alternative splicing (AS) is closely associated with tumor development and the tumor immune microenvironment. However, to date, there is no comprehensive analysis of AS and the prognosis and immunological features of BLCA. Method: In this study, we downloaded RNA-Seq data and clinical information from The Cancer Genome Atlas (TCGA) database, and AS events were acquired from the TCGA Splice-seq. A total of eight prognostic AS events ((C19orf57|47943|ES, ANK3|11845|AP, AK9|77203|AT, GRIK2|77096|AT, DYM|45472|ES, PTGER3|3415|AT, ACTG1|44120|RI, TRMU|62711|AA) were identified during univariate and lasso regression analyses and used to construct a risk score model. Results: The Kaplan-Meier analysis revealed that the high-risk group had a worse prognosis than the low-risk group. The areas under the curves (AUCs) of Receiver operating characteristic (ROC) curves for this risk score model for 1-year, 3-year, and 5-year were 0.698, 0.742, and 0.772, respectively. One of the prognostic AS event-related genes, TRMU, was differentially expressed between tumor tissues and normal tissues in BLCA. The ssGSEA and CIBERSORT algorithm showed that both the risk score model and TRMU were significantly associated with the tumor immune microenvironment, immune status (immune cells, immune-related pathway, and immune checkpoint) in BLCA patients. The TIMER database confirmed the relationship between the expression of TRMU and immune cells and checkpoint genes. Furthermore, Cytoscape 3.8.0 was used to construct the regulatory network between AS and splicing factors (SFs). Conclusion: Our study demonstrated that AS events were powerful biomarkers in determining the prognosis and immune status in BLCA and may be potential therapeutic targets in BLCA.